ANTIBIOTIC MISUSE AND ANTIMICROBIAL RESISTANCE KNOWLEDGE AMONG UNIVERSITY STUDENTS IN BANGLADESH: CURRENT TRENDS AND FUTURE PROSPECTS - Bhuiyan, Md. Rimon; Ali, Md. Niamot; Hiya, Nazmush Shayer; Khatun, Asma; Shafiq, Sadia Binte; Shimi, Syeda Shamapika Ahmed; Fahim, Md Muhtasim Munif; Hasan, Imtiaj (Science Journal of University of Zakho, 2026)
Antimicrobial resistance (AMR) is a growing global health concern threatening both human and animal health. Misuse and overuse of antibiotics, especially through self-medication, are major contributors in developing countries. This study aimed to assess the knowledge, attitude, and practices regarding antibiotic misuse and AMR among university students in Bangladesh. A cross-sectional questionnairebased survey was conducted from September 2024 to February 2025 among 398 students from different disciplines at the University of Rajshahi. Systematic random sampling was applied, and the data were analyzed by using SPSS, version 27, to identify associations with socio-demographic factors. Overall knowledge of antibiotics and AMR was unsatisfactory. While 90.7% of students knew about antibiotics, only 64.07% and 63.32% were aware of antimicrobial drugs and AMR, respectively. Science students showed significantly higher AMR awareness (p
Keywords: Antimicrobial resistance; Antibiotic misuse; Self-medication; Irrational antibiotic use; Knowledge and attitudes